Association of maternal and child health related variables with decline in infant mortality rate in Punjab, India - Kaur, Harjot; Singh, Tarundeep; Lakshmi, PVM (International Journal Of Community Medicine And Public Health, 2017)
Background: Infant mortality rate (IMR) is a sensitive indicator for monitoring child health and survival. Punjab state in North India is performing better than most of the other states in various health indicators. Punjab’s IMR has shown a rapid decline from 38/1000 live births in 2008 (Sample registration system (SRS) 2008) to 24/1000 live births in 2014 (SRS 2014). This study was planned to assess which of the maternal and child health services is associated with rapid decline in infant mortality rate. Methods: Association between various components of prenatal care, intranatal care and postnatal care, and child healthcare and socio demographic variables (taken from secondary data of District Level Household Surveys) and Infant Mortality Rate (taken from SRS) of Punjab was studied. Spearman correlation coefficient was calculated to measure the association between the variables. Results: Total fertility rate (TFR), women who had institutional deliveries, safe deliveries and mean children ever born are statistically significantly associated with decline in infant mortality rate. Conclusions: In Punjab, maternal and child health indicators are directly or indirectly associated with decline in infant mortality rate. Findings of the study demonstrate that the recent rapid decline in IMR of Punjab is strongly associated with increase in institutional deliveries and decline in TFR and the mean number of children ever born.